On vibration analysis of functionally graded carbon nanotube reinforced magneto-electro-elastic plates with different electro-magnetic conditions using higher order finite element methods - M. Vinyas (Defence Technology, 2021)
This article deals with evaluating the frequency response of functionally graded carbon nanotube reinforced magneto-electro-elastic (FG-CNTMEE) plates subjected to open and closed electro-magnetic circuit conditions. In this regard finite element formulation has been derived. The plate kinematics adjudged via higher order shear deformation theory (HSDT) is considered for evaluation. The equations of motion are obtained with the help of Hamilton’s principle and solved using condensation technique. It is found that the convergence and accuracy of the present FE formulation is very good to address the vibration problem of FG-CNTMEE plate. For the first time, frequency response analysis of FG-CNTMEE plates considering the effect of various circuit conditions associated with parameters such as CNT distributions, volume fraction, skew angle, aspect ratio, length-to-thickness ratio and coupling fields has been carried out. The results of this article can serve as benchmark for future development and analysis of smart structures.